12 weeks to a sharper you : a guided program - Gupta, Sanjay, 1969-; Loberg, Kristin (Simon & Schuster Paperbacks, 2022)
"Dr. Sanjay Gupta helped countless readers keep their brains sharp and effortlessly productive with Keep sharp : build a better brain at any age. In 12 Weeks to a Sharper You, he now provides a step-by-step 12-week program to help you put his transformational ideas into daily practice. He writes, "Change is a challenge, and changing long-established habits takes effort." But this workbook makes it easy to apply Gupta's groundbreaking tips and research to establish healthy behaviors for life. The 12-week program will help you feel less anxious, sleep better, improve energy, think more clearly, and become more resilient to daily stress"--